2021
DOI: 10.1021/acsami.1c02834
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Invisible Ultrasmall Gold Nanoparticles—Framework for Synthesis and Evaluation

Abstract: Nanomedicine is seen as a potential central player in the delivery of personalized medicine. Biocompatibility issues of nanoparticles have largely been resolved over the past decade. Despite their tremendous progress, less than 1% of applied nanosystems can hit their intended target location, such as a solid tumor, and this remains an obstacle to their full ability and potential with a high translational value. Therefore, achieving immune-tolerable, blood-compatible, and biofriendly nanoparticles remains an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…NP recognition by phagocytes is mediated through protein opsonisation. This means that the formation and composition of an NP's corona greatly determines its uptake by the MPS [7]. The conventional approach to reducing phagocyte recognition involves the use of antifouling and hydrophilic polymers, such a polyethylene glycol (PEG) and zwitterionic polymers, to cloak the surface of the NPs, whereas true bioinvisibility requires the presence Glossary α-phase half-life: the time it takes for the plasmon concentration of a drug to drop by half due to the rapid redistribution from the central to the peripheral compartments.…”
Section: What Do We Know About Np Clearance?mentioning
confidence: 99%
“…NP recognition by phagocytes is mediated through protein opsonisation. This means that the formation and composition of an NP's corona greatly determines its uptake by the MPS [7]. The conventional approach to reducing phagocyte recognition involves the use of antifouling and hydrophilic polymers, such a polyethylene glycol (PEG) and zwitterionic polymers, to cloak the surface of the NPs, whereas true bioinvisibility requires the presence Glossary α-phase half-life: the time it takes for the plasmon concentration of a drug to drop by half due to the rapid redistribution from the central to the peripheral compartments.…”
Section: What Do We Know About Np Clearance?mentioning
confidence: 99%
“…[27][28][29][30] Conversely, nanoparticles that are smaller than 10 nm ("ultrasmall" nanoparticles) exhibit different behavior from larger nanoparticles. [31] Ultrasmall nanoparticles are cleared through the kidneys -an elimination route that is faster than the hepatic accumulation and slow metabolism of larger nanoparticles. [32][33][34]31] While this leads to lower accumulation in off-target organs (i.e., decreased off-target toxicity), it also decreases accumulation in the target organ (e.g., tumor).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these results indicated that MXenes can be detected in immune cells without affecting cell functionality, unlike other nanomaterials that can boost the immune system responses, altering cell functions. [28,[40][41][42][43] The good biocompatibility of MXenes, is probably due to their favorable chemistry. In particular, Ti-, Nb-, Mo-, and Ta-based MXenes selected in this study, are all composed by biocompatible transition metals used in medical settings as metal alloy implants, contrast agents, and biomaterial surface coatings.…”
Section: Mxenes Do Not Affect Immune Cell Functionalitymentioning
confidence: 99%